Broadband Multifunctional Plasmonic Logic Gates. Issue 13 (16th April 2018) - Sang, Yungang; Wu, Xiaojia; Raja, Soniya S.; Wang, Chun‐Yuan; Li, Haozhi; Ding, Yufeng; Liu, Dahe; Zhou, Jing; Ahn, Hyeyoung; Gwo, Shangjr; Shi, Jinwei
Abstract: Plasmonic logic gates provide a promising platform to realize diffraction‐unlimited all‐optical logic circuits. However, previous plasmonic logic gates suffer from narrow bandwidth and high loss. Here, broadband plasmonic logic gates are proposed and demonstrated using a unique design based on curved silver gratings. These logic gates can maintain a high intensity contrast ratio (29 dB) under front optical illumination. And, the broadband feature is achieved due to the feature of zero optical path difference from different positions of the curved grating to the output port. All the seven fundamental logic gates are demonstrated. In addition, different types of logic gates can be realized using the same device configuration. The possibility of multifunctionality makes these logic gates easy for device fabrication and system integration. Abstract : Plasmonic logic gates provide a promising platform to realize diffraction‐unlimited all‐optical logic circuits. Here, broadband plasmonic logic gates are proposed and demonstrated using a unique design based on curved silver gratings. All the seven fundamental logic gates have been demonstrated using the same device configuration. The possibility of multi‐functionality makes these logic gates easy for device fabrication and system integration.